Corneal Ulcers in Dogs - Treatment with the Synthetic Polymer PBAT - Rodrigues, Giovanna Giuffrida; Pereira, Aline Cardoso; Moretti, Marcela Fernanda; Lucas, Alessandra de Almeida; Bretas, Rosário Elida Suman; Andrade, Alexandre Lima de (Acta Scientiae Veterinariae, 2024)
Background: Ulcerative keratitis is a common condition in dogs that, if untreated, can cause dog’s loss of vision. The use of natural or synthetic polymer-based membranes has become a feasible alternative for the treatment of this injury due to their biodegradability, sustentability, non-toxicity and excellent mechanical properties as good resistance to impact and flexibility, being able to be used for medical applicances. This work aimed at evaluating the clinical effect of the poly (butylene-adipate-co-terephtalate) (PBAT) and thermoplastic starch (TPS) membrane as synthetic graft in lamelar kerato- plasty technique for the treatment of corneal ulcer in dogs. Materials, Methods & Results: This study included 6 dogs that, after pre-surgery exams, were underwent to lamelar keratoplasty with application of PBAT/TPS membrane on the injuried site. They were undergone to ophthalmological exams before the surgery (M0) as well as in the 3rd, 7th, 15th and 30th postoperative days (M3, M7, M15 and M30, respectively). Postoperative evaluations showed that blepharospasm was mild till M3, becoming absent in M30; while ocular secretion was slightly present till M7, being absent since then. Conjunctival hyperemy was intense in M0, diminishing gradually till M15. Clinical signs of corneal vascularization were observed from M7, becoming remarkably intense in M15. After membrane removal, corneal cicatrization was observed as well as the integrity of eye bulb’s structure. Discussion: The clinical evolution of the animals submitted to the treatment with the membrane of PBAT/ TPS was similar to that reported by already established techniques, such as: free conjunctival graft and pediculated or with use of sardine scale and preserved renal capsule. In both, there was good corneal healing and there were no lesions of collanolytic pattern (melting type), no clinical signs of membrane extrusion The preference for the use of the PBAT/TPS membrane in the ratio 60:40 was due to the fact that it has a more malleable texture, that would be more comfortable in the eyes of the animals included in the study, in addition to being used in the clinical treatment of other conditions. In addition, the proportionof TPS added to PBAT (40:60) was based on the best results regarding costs, performance and biodegradability, since the tensile strength of TPS remains stable at concentrations lower than 10% and higher than 30%. For the application of the membrane, a continuous suture pattern was used, sometimes interrupted, varying according to its accommodation in the ulcer bed and curvature of the cornea. Among the parameters evaluated are corneal vascularization, which, all cases, increased and reached its peak in M15, allowing to infer that the presence of the membrane exerts a chronic local inflammatory stimulus, which coincides with the peak of angiogenic stimulation of the cornea in the patients included in the study. Blepharospasm, although present, was considered mild until the third day of evaluation, becoming absent until the end of clinical observation (M30). The conjunctival hyperemia observed is common in acute conjunctivitis, so its occurrence was already expected with the surgical procedure. The predominance of mucoid secretion found in these patients was probably due to conjunctival inflammatory process associated with the severity of ulcers and underlying diseases, which triggered the stimulation of goblet cells. With the correction of these occurrences during the membrane placement procedure, the secretion was over. So, it is possible to conclude that PBAT/TPS membrane is a feasible therapeutic alternative for corneal ulcer treatment in animals. Keywords: keratoplasty, synthetic polymers, ulcerative keratitis, dogs. Título: Úlceras de córnea em cães - tratamento com o polímero sintético PBAT Descritores: ceratoplastia, polímeros sintéticos, ceratite ulcerativa, cães.